Pemanfaatan Gel Lidah Buaya (Aloe chinensis L.) yang Diaplikasikan dengan Gliserin sebagai Bahan Pelapis Buah Pisang Barangan (Musa acuminata L.) - Riza Linda, Yuke Zafika, Mukarlina (Universitas Tanjungpura, 2015)
Aloe vera gel (Aloe chinensis L.) is a polysaccharise that contains a lot of inhibitor components for postharvest damage in fresh food products and is capable of maintaining humidity by means of controlling the water loss. The material that can be combined with the coating material to maintain the compound of the Aloe gel is glycerine. This research aims to find out the influence of coating materials of Aloe vera gel bu adding glycerine to the storage of barangan banana (Musa acuminata L.). The research was conducted from April to July 2014. It employed a Completely Randomized Design with 7 concentration of glicerine (0%, 5%, 6%, 7%, 8%, 9%, 10%). Analysis results showed that the educed weight of the banana covered with a mix of Aloe vera gel and glycerin of 75 was 6,75%. The banana skin color covered with a mix of Aloe vera gel and glycerin of 7% resulted in a score of 22. The organoleptic test resulted in the aroma score of 5,00-5,47 and flavor of 5,18-5,71 which means the banana is somewhat favored by consumers. The Kruskal-Wallis analysis results continued with Nemenyi test on the banana glucose level showed that the banana coated with a mix of Aloe vera gel and glycerin 7% had a glucose level of 4,5% on the 12th day of observation.Keywords: Aloe vera